Pengaruh Kepemilikan Manajerial dan Komisaris Independen Terhadap Nilai Perusahaan Dengan CSR sebagai Variabel Mediasi - Ardianti, Yunita; Akram, Akram; Surasni, Surasni (E-Jurnal Akuntansi, 2019)
This study aims to determine the effect of managerial ownership and independent commissioners on corporate value through CSR. This research was conducted at mining companies listed on the Indonesia Stock Exchange for the period 2016-2017. The population in this study were 82 companies and 36 research samples using purposive sampling method. This study uses path analysis with SPSS 23. Analysis tools. The results of this study indicate that managerial ownership and independent commissions influence CSR simultaneously. Managerial ownership, independent commissioners and CSR have no effect on company value simultaneously. Managerial ownership does not partially affect CSR and companyvalue. Independent commissioners do not partially influence CSR and company value. Keywords:  Corporate Value, CSR, Managerial Ownership, Independent    Commissioner